STRATEGI PENGEMBANGAN MUARE ULAKKAN NIGHT FESTIVAL SEBAGAI ATRAKSI WISATA KABUPATEN SAMBAS - Nur Astri Fatihah; Hikmah Trisnawati; Tendi Antopani (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2023)
Performing cultural products in the form of festivals is one of the tourism products that provides significant impacts in increasing regional tourism attractiveness. Festivals are held in many places in the world, including Sambas Regency, one of which is through the Muare Ulakan Night Festival. Muare Ulakan Night Festival 2023 is a competition and parade event for ornamental boats along the Sambas River, especially on the path in front of the Alwatzikhoebillah Palace to the waterfront area. This activity was attended by 38 participants of ornamental boats and ships. Although this activity has the potential to be a popular tourist attraction, based on observations and interviews with organizers there are several things that are still a problem in its development. This research aims to identify internal and external factors in Muare Ulakan Night Festival and find its development strategy as a tourist attraction in Sambas Regency. Data in this study were collected from observation, documentation study, and interviews with seven informants purposively. By using SWOT analysis, several weaknesses and opportunities were found which were used as a starting point to formulate a development strategy for the Muare Ulakan Night Festival as a tourist attraction.